Peran Guru Dalam Mengatasi Kesulitan Membaca Al-Qur’an Pada Siswa di Sekolah Dasar Islam - Fusiroh, Fusiroh; Rokhmah, Siti; Rahman, Hendra Yulia; Taslim, Muhammad; Marhani (IAIN PAREPARE, 2023)
Teachers as an element in education not only play an important role as agents who provide knowledge but also as agents who provide assistance and support for students to overcome difficulties in the learning process. Teachers often become subjects, especially in discourses that discuss management, character building, and the effectiveness of the learning process so that the discourse of teachers as subjects who have a role in overcoming student difficulties tends to be neglected in scientific discussions. In line with that, this study focuses on the question